A comprehensive review of hydrocarbons and genetic model of the sandstone‐hosted Dongsheng uranium deposit, Ordos Basin, China. Issue 3 (15th July 2016) - Cao, B. F.; Bai, G. P.; Zhang, K. X.; Zhang, L. K.; He, B.
Abstract: The Dongsheng uranium deposit, the largest in situ leach uranium mine in the Ordos Basin, geometrically forms a roll‐front type deposit that is hosted in the Middle Jurassic Zhiluo Formation. The genesis of the mineralization, however, has long been a topic of great debate. Regional faults, epigenetic alterations in surface outcrops, natural oil seeps, and experimental findings support a reducing microenvironment during ore genesis. The bulk of the mineralization is coffinite. Based on thin‐section petrography, some of the coffinite is intimately intergrown with authigenic pyrite (ore‐stage pyrite) and is commonly juxtaposed with some late diagenetic sparry calcite (ore‐stage calcite) in primary pores, suggesting simultaneous precipitation. Measured homogenization temperatures of greater than 100°C from fluid inclusions indicate circulation of low‐temperature hydrothermal fluids in the ore zone. The carbon isotopic compositions of late calcite cement (δ 13 CVPDB  = −31.0 to −1.4‰) suggest that they were partly derived from sedimentary organic carbon, possibly from deep‐seated petroleum fluids emanating from nearby faults. Hydrogen and oxygen isotope data from kaolinite cement (δD = −133 to −116‰ and δ 18 OSMOW  = 12.6–13.8‰) indicate that the mineralizing fluids differed from magmatic and metamorphic fluids and were more depleted in D ( 2 H) than modern regional meteoric waters. Such a strongly negative hydrogen isotopic signature suggests that there has been selective modification of δD by CH4 ±H2 S±H2 fluids. Ore‐stage pyrite lies within a very wide range of δ 34 S (−39.2 to 26.9‰), suggesting that the pyrite has a complex origin and that bacterially mediated sulfate reduction cannot be precluded. Hydrocarbon migration and its role in uranium reduction and precipitation have here been unequivocally defined. Thus, a unifying model for uranium mineralization can be established: Early coupled bacterial uranium mineralization and hydrocarbon oxidation were followed by later recrystallization of ore phases in association with low‐temperature hydrothermal solutions under hydrocarbon‐induced reducing conditions.